1994
DOI: 10.1021/jm00044a017
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Cyclic Amide-Linked Analogs of Angiotensins II and III

Abstract: Cyclic amide-linked angiotension II (ANGII) analogues have been synthesized by novel strategies, in an attempt to test the ring clustering and the charge relay bioactive conformation recently suggested. These analogues were synthesized by connecting side chain amino and carboxyl groups at positions 1 and 8, 2 and 8, 3 and 8, and 3 and 5, N-terminal amino and C-terminal carboxyl groups at positions 1 and 8, 2 and 8, and 4 and 8, and side chain amino to C-terminal carboxyl group at positions 1 and 8. All these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…Related work in our laboratory has led to the design and synthesis of cyclic analogues for guinea pig MBP 72-85 , Thrombin receptor motif SFLLR, Angiotensins II and III, and GnRH (unpublished) which were able to maintain or suppress the biological function of the original peptide. 15,20,[23][24][25][26][27][28] We had previously demonstrated that injection of Lewis rats with linear or cyclic guinea pig MBP 72-85 peptides induced EAE. 19 15 In our in vivo rat studies, EAE was induced by the agonist guinea pig epitope MBP [72][73][74][75][76][77][78][79][80][81][82][83][84][85] and not by the human MBP 83-99 agonist peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Related work in our laboratory has led to the design and synthesis of cyclic analogues for guinea pig MBP 72-85 , Thrombin receptor motif SFLLR, Angiotensins II and III, and GnRH (unpublished) which were able to maintain or suppress the biological function of the original peptide. 15,20,[23][24][25][26][27][28] We had previously demonstrated that injection of Lewis rats with linear or cyclic guinea pig MBP 72-85 peptides induced EAE. 19 15 In our in vivo rat studies, EAE was induced by the agonist guinea pig epitope MBP [72][73][74][75][76][77][78][79][80][81][82][83][84][85] and not by the human MBP 83-99 agonist peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of ex vivo experiments using the rat uterus assay, we have shown that the cyclic ANG II analogue [Sar~,Asp3,LysS]ANG II has contractile activity (-30% of ANG II) [5]. In the present study, another similar cyclic ANG II analogue, namely [SarI,Lys3,GluS]ANG II, was found to have contractile activity in the rat uterus assay (-15% of ANG II) and to produce an immediate and sustained blood pressure elevation after iv administration in anesthetized rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine horns from diethylstilbestrol-primed virgin Sprague-Dawley rats (150-250 g) were used in the experiment carried out as previously described [5]. Agonist activity was determined by matching the response with an equivalent response to ANG II (human).…”
Section: Rat Uterus Bioassaymentioning
confidence: 99%
See 2 more Smart Citations